2004
DOI: 10.1093/pcp/pch094
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Photosynthetic Activities is Triggered by Loss of a Small Amount of Water in a Desiccation-Tolerant Cyanobacterium, Nostoc commune

Abstract: Changes in photosynthetic activities under hypertonic conditions were studied in a terrestrial, highly desiccation-tolerant cyanobacterium, Nostoc commune, and in some desiccation-sensitive cyanobacteria. The amounts of water sustained in the colony matrix outside the N. commune cells and the cellular solute concentration were estimated by measuring the water potential, and the solute concentration was supposed to correspond to around 0.22 M sorbitol. Incubation of the colonies in 0.8 M sorbitol solution inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 18 publications
4
41
0
Order By: Relevance
“…h Data from a previous report (Satoh et al, 2002). Data from a previous report (Hirai et al, 2004). activity and photosynthetic electron flow of the cyanolichen C. subflaccidum were observed (Fig.…”
Section: External Osmotic Pressure and Photosynthesis In Cyanolichensmentioning
confidence: 67%
See 2 more Smart Citations
“…h Data from a previous report (Satoh et al, 2002). Data from a previous report (Hirai et al, 2004). activity and photosynthetic electron flow of the cyanolichen C. subflaccidum were observed (Fig.…”
Section: External Osmotic Pressure and Photosynthesis In Cyanolichensmentioning
confidence: 67%
“…An increase in compatible solutes prevents water loss or increases water uptake from the air when humidity is high (Lange et al, 1988). It has been observed, however, that the intracellular solute concentration is low (corresponding to a sorbitol concentration of approximately 0.22 M) in the desiccation-tolerant terrestrial cyanobacterium Nostoc commune (Satoh et al, 2002;Hirai et al, 2004). N. commune photosynthetic activity is lost when incubated in low sorbitol concentrations (Hirai et al, 2004), whereas a Trebouxia spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its thalli covered up to 50% of uncovered, moist soil in the analyzed habitats. In polar regions N. commune may occur in a water environment in associ− ation with mosses, but, above all, it is an obligatory taxon for surface habitats (Howard−Williams et al 1986;Fumanti et al 1995;Hirai et al 2004, Fukunda et al 2008, Komárek J. and Elster 2008Komárek O. and Komárek J. 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Qian et al (1989) have reported that the recovery of photosynthesis occurs mainly during the rainy season in which the recovered photosynthesis provides compounds and energy for the growth and reproduction of N. flagelliforme. Many studies on the photosynthetic function of Nostoc commune in response to dehydration and rehydration have been performed (Hirai et al, 2004;Satoh et al, 2002), but the rate of photosynthesis recovery in N. flagelliforme was shown to be more rapid than that in N. commune (Scherer et al, 1984). Previous studies showed that the photosynthetic resumption of N. flagelliforme not only depended on light, potassium, and water (Gao et al, 1998b;Huang et al, 2005;Qiu and Gao, 1999), but also required de novo protein synthesis (Qiu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%